THE TO BE A TEACHER AND BEING PROFESSIONAL: THE IDENTIFICATION WITH THE KNOWLEDGE AND THE COMMITMENT WITH THE LEARNING. (Fiep Bulletin - online, 2015)
The present work has as focus the study of as feels the identification with the knowledge and the commitment with the learning, of the teachers of the educational universe, that act in the fundamental teaching of the city of Piraju and as they are positioned front to the new pertinent knowledge to the pedagogic area. Starting from theoretical foundations, identified as felt the learning process and the formation, that it originated your practice pedagogic static, that despises the vision where each individual, through the learning, it is inserted in an organized way in the world as active participant, when appropriating of knowledge and techniques, that makes possible to build in your interior an universe of symbolic representations. And, that therefore, it is done indispensable a critical positioning on that and as the school it reproduces this knowledge, as to depart from the study of the point of view of who teaches and of who learns, still embracing, the participation of the family and of the society, that overtime will be analyzed through the answers obtained in interviews accomplished with those actors. During the period of 2006-2007, it will be rendering if the steps that will take to the attainment of that work. pursuing the roads, that will take me to the accomplishment and conclusion of this work.       The reflection on that thematic one, felt starting from the accomplishment of the work of conclusion of specialization course in psicopedagogia, in a school unit of the city of Piraju, opportunity in the which was possible to notice that the teachers were positioned without the due commitment in the schedules of HTPC (Schedule of Collective Pedagogic Work), moment this reserved for studies, elaboration of class plans and debates on how to apply the contents proposed in the plannings. Fact, that created the ambiguity, theory and practice making unfeasible embracing of new knowledge.
Keywords: identification; knowledge and commitment.